Efficacy and safety of olmesartan medoxomil‐amlodipine besylate tablet in Chinese patients with essential hypertension: A prospective, single‐arm, multi‐center, real‐world study - Zhaoqiang Cui; Zhaohui Qiu; Wenli Cheng; Wei Hu; Genshan Ma; Xiaojun Cai; Yafei Jin; Yi Zhao; Liqun He; Ying Li; Peili Bu; Xiaoping Chen; et al. (The Journal of Clinical Hypertension, 2024)
Abstract There lacks real‐world study with a large sample size assessing olmesartan medoxomil‐amlodipine besylate (OM‐AML) tablet. Therefore, this study aimed to evaluate the efficacy and safety of OM‐AML tablet in patients with essential hypertension. Totally, 1341 patients from 36 medical centers with essential hypertension who took OM‐AML (20/5 mg) tablet were analyzed in the current prospective, single‐arm, multi‐center, real‐world study (SVK study). Seated systolic blood pressure (SeSBP) and seated diastolic blood pressure (SeDBP) at baseline, week (W)4 and W8 were measured. The mean (±SE) change of SeSBP/SeDBP was ‐10.8 ± 0.4/‐6.6 ± 0.3 mmHg at W4 and ‐12.7 ± 0.5/‐7.6 ± 0.3 mmHg at W8, respectively. At W4, 78.8% and 29.0% patients achieved BP target by China and American Heart Association (AHA) criteria; at W8, 84.7% and 36.5% patients reached blood pressure (BP) target by China and AHA criteria, accordingly. Meanwhile, 80.2% and 86.4% patients achieved BP response at W4 and W8, respectively. Home‐measured SeSBP and SeDBP decreased from W1 to W8 (both p < .001). Besides, patients’ and physicians’ satisfaction were elevated at W8 compared with W0 (both p < .001). The medication possession rate was 94.8% from baseline to W4 and 91.3% from baseline to W8. The most common drug‐related adverse events were nervous system disorders (4.6%), vascular disorders (2.6%), and general disorders and administration site conditions (2.3%) by system organ class, which were generally mild and manageable. In conclusion, OM‐AML tablet is one of the best antihypertensive agents in patients with essential hypertension.